Diversity and role of woody non-timber forest products in Doba District, Eastern Ethiopia - AMARE FASSIL ABEBAW; PATRICK VAN DAMME (Smujo International, 2023)
Abstract. Abebaw AF, Damme PV. 2023. Diversity and role of woody non-timber forest products in Doba District, Eastern Ethiopia. Nusantara Bioscience 15: 38-47. Non-Timber Forest Products (NTFP) play a pivotal role as local sources of medicine, household paraphernalia, and fodder and offer income opportunities that can mitigate poverty. This study was conducted in Doba District, West Hararghe Zone, Eastern Ethiopia, to analyze the diversity and economic contribution of non-timber forest products. Both ethnobotanical and vegetation data were cross-sectionally collected from February 2020 up to June 2021. A total of 422 informants selected randomly from forest inhabitants were interviewed using semi-structured questionnaires to explore NTFP utilization and their economic contributions. Vegetation data were collected from 56 sample plots of each 20m x 20m (400m2) along transects lines. Vegetation data collected were analyzed for the relative density of species, Shannon-Wiener index, species evenness, and relative frequency. From the household survey, 58 plant species categorized in 55 genera and 35 families were identified as NTFP-bearing species. Analysis of the socio-economic data shows that NTFP collection is a day-to-day activity of the local communities. These communities use NTFPs in different types of use categories, namely medicinal plants (32, 55.17%), melliferous species (20, 34.48%), wild food and condiment species (22, 37.93%), farm implements (7, 12.06%), wood and flavoring (6, 10.34%), source of energy (20, 35.71%), and household utensils and construction materials (30, 51.72%). The market survey analysis showed that NTFPs account for about 15.77% of the annual household income. The vegetation survey showed that Ades Forest has a good status with an average density of 1,450 plants ha-1, high Shannon-Wiener index (H =3.299), and species evenness (E = 0.81). Ades Forest harbors a diverse number of NTFP-bearing species used for several categories. The study reveals the real experiences of the local communities in utilizing NTFPs for their livelihood. Forest dependency rates tend to be higher among poor households. However, further study on production potential and market chain analysis should be done together with awareness creation activities to get a sustainable product for the community and conserve the forest resource.